Syringic acid, a novel thyroid hormone receptor‐β agonist, ameliorates propylthiouracil‐induced thyroid toxicity in rats. Issue 8 (28th May 2021) - Panda, Sunanda; Kar, Anand; Singh, Meenakshi; Singh, Ram Kumar; Ganeshpurkar, Ankit
Abstract: The aim of this study was to evaluate the potential of syringic acid (SA) against propylthiouracil (PTU)‐induced hypothyroidism in rats. SA at a prestandardized dose, 50 mg/kg/day, was orally administered to PTU‐induced hypothyroid rats for 30 days, and alterations in the levels of serum triiodothyronine (T3 ), thyroxine (T4 ), thyrotropin (TSH), alanine transaminase (ALT), and aspartate transaminase (AST); tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6); total cholesterol (CHOL) and triglycerides (TG); hepatic lipid peroxidation (LPO) and antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and glutathione content), as well as histological changes in liver and thyroid were examined. The molecular interactions of the ligand, SA, with thyroid‐related protein targets, such as human thyroid hormone receptor β (hTRβ), and thyroid peroxidase (TPO) protein, were studied using molecular docking. Whereas in hypothyroid animals, T4, T3, and antioxidants were decreased, there was an increase in TSH, TNF‐α, IL‐6, ALT, AST, and hepatic LPO; administration of SA in PTU‐induced animals reversed all these indices to near normal levels. SA also improved the histological features of liver and thyroid gland. Our study clearly demonstrates SA as a novel thyroid agonist for augmenting the thyroid functions in rats. Molecular docking analysis reveals that SA possesses good binding affinity toward both the targets, hTRβ and TPO. Through this approach, for the first time we provide the evidence for SA as a novel thyroid agonist and suggest a receptor‐mediated mechanism for its thyroid stimulatory potential.